The Influence of Location and Promotion on Purchasing Decisions (Case Study on Sarua Keneh Consumers Payakumbuh City) - Syuryatman Desri; Azizah Nur; Reivany Sannia (PT FORMOSA CENDEKIA GLOBAL, 2023)
The purpose of this study was to identify the effect of location and promotion on purchasing decisions at Sarua Keneh Payakumbuh City simultaneously and partially. Hypothesis testing was carried out using the T, F, and R2 tests. The results showed that location and promotion simultaneously had a significant effect on purchasing decisions for Sarua Keneh, Payakumbuh City. Partially, location has a significant effect on the purchasing decision of Sarua Keneh Payakumbuh City, while promotion has no significant effect on the brand Sarua Keneh Payakumbuh City.